Studi Penerapan dan Evaluasi Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) Berdasarkan Peraturan Pemerintah No. 50 Tahun 2012 di PT Petro Oxo Nusantara (PON) - Rani Nur Qurotu A'yuni; Nihlatul Falasifah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The petrochemical industry is a high-risk sector that requires comprehensive implementation of Occupational Safety and Health (OSH). PT Petro Oxo Nusantara (PT PON) is the sole producer of 2-EH (Ethyl Hexanol), NBA (Normal-Butanol), and IBA (Iso-Butanol) in Indonesia and Southeast Asia. The purpose of this study is to understand and evaluate the implementation of the Occupational Safety and Health Management System (SMK3) based on Government Regulation No. 50 of 2012. The methods used were observation, interviews, and direct participation in OSH operational activities at PT PON. The evaluation results of 166 criteria in 12 elements of SMK3 showed an achievement of 156 points (93.98%), which is classified as “Satisfactory”. PT. Petro Oxo Nusantara also has ISO 45001:2018 certification and Zero Accident awards for 2023 and 2024. The implementation of the OHSMS reflects a commitment to six integrated management systems (ISO 9001, LCO, OHSMS, ISO 14001, Halal, ISO 37001) to achieve sustainable OHS, as well as improvements in policies, training, and internal reporting. This study confirms that SMK3 at PT PON has been effectively implemented and can serve as a reference for similar industries in creating a safe, healthy, and productive work environment, with recommendations for periodic evaluation of points that have not been met and expanding training as further research.